Allergic diseases among children: nutritional prevention and intervention - Hendaus MA; Jomha FA; Ehlayel M (Dove Medical Press, 2016)
Mohamed A Hendaus,1,2 Fatima A Jomha,3 Mohammad Ehlayel2,4 1Department of Pediatrics, Section of Academic General Pediatrics, Hamad Medical Corporation, 2Weill Cornell Medical College, Doha, Qatar; 3School of Pharmacy, Lebanese International University, Khiara, Lebanon; 4Department of Pediatrics, Section of Pediatric Allergy-Immunology, Hamad Medical Corporation, Doha, Qatar Abstract: Allergic diseases comprise a genetically heterogeneous group of chronic, immunomediated diseases. It has been clearly reported that the prevalence of these diseases has been on the rise for the last few decades, but at different rates, in various areas of the world. This paper discusses the epidemiology of allergic diseases among children and their negative impact on affected patients, their families, and societies. These effects include the adverse effects on quality of life and economic costs. Medical interest has shifted from tertiary or secondary prevention to primary prevention of these chronic diseases among high-risk infants in early life. Being simple, practical, and cost-effective are mandatory features for any candidate methods delivering these strategies. Dietary therapy fits this model well, as it is simple, practical, and cost-effective, and involves diverse methods. The highest priority strategy is feeding these infants breast milk. For those who are not breast-fed, there should be a strategy to maintain beneficial gut flora that positively influences intestinal immunity. We review the current use of probiotics, prebiotics, and synbiotics, and safety and adverse effects. Other dietary modalities of possible potential in achieving this primary prevention, such as a Mediterranean diet, use of milk formula with modified (hydrolyzed) proteins, and the role of micronutrients, are also explored. Breast-feeding is effective in reducing the risk of asthma, allergic rhinitis, and atopic eczema among children. In addition, breast milk constitutes a major source of support for gut microbe colonization, due to its bifidobacteria and galactooligosaccharide content. The literature lacks consensus in recommending the addition of probiotics to foods for prevention and treatment of allergic diseases, while prebiotics may prove to be effective in reducing atopy in healthy children. There is insufficient evidence to support soy formulas or amino acid formulas for prevention of allergic disease. A healthy diet, such as the Mediterranean diet, may have a protective effect on the development of asthma and atopy in children. In children with asthma and allergic diseases, vitamin D deficiency correlates strongly with asthma, allergic rhinitis, and wheezing. Keywords: allergic, children, prebiotics, primary, probiotics, prevention, synbiotics